An Analysis of breakthrough seizures and related factors in pediatric epilepsy patients - Khalid, Hina; Arif, Saeed; Hashmat, Asif; Shaheer Arif; Farrukh, Huma (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the frequency of breakthrough seizures among paediatric patients suffering from epilepsy, and factors related to theprecipitation of these seizures. Method: The cross-sectional study was conducted from July 1, 2018, to July 1, 2020, at the Combined Military Hospital Lahore and the Military Hospital, Rawalpindi, Pakistan, and comprised children of either gender aged 2-12 years diagnosed with any type of epilepsy presenting at the children outpatient department. Diagnosis of epilepsy was established by either a consultant adult neurophysician or a consultant paediatrician. The presence of breakthrough seizures was assessed by obtaining detailed history from the patient and the primary caregiver. Socio-demographic profile, duration of epilepsy and poly-pharmacy were noted. Data was analysed using SPSS 23. Results: Of the 450 subjects, 259(57.6%) were boys and 191(42.4%) were girls. The overall mean age was 6.353±4.732 years. The presence of breakthrough seizures was noted in 227(50.4%) subjects. Children with young age, with low family income, and those in need of poly-pharmacy showed significantly higher odds for breakthrough seizures (p<0.05). Conclusion: The incidence of breakthrough seizures in epileptic children was high despite the anticonvulsant agents that were previously effective in controlling seizures. Key Words: Breakthrough seizures, Childhood epilepsy, Anticonvulsants, Risk factors. Continuous...